2009
DOI: 10.1029/2009gl037595
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of whistler‐mode chorus waves observed on the THEMIS spacecraft

Abstract: [1] Whistler mode chorus waves are receiving increased scientific attention due to their important roles in both acceleration and loss processes of radiation belt electrons. A new global survey of whistler-mode chorus waves is performed using magnetic field filter bank data from the THEMIS spacecraft with 5 probes in near-equatorial orbits. Our results confirm earlier analyses of the strong dependence of wave amplitudes on geomagnetic activity, confinement of nightside emissions to low magnetic latitudes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

74
461
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 306 publications
(536 citation statements)
references
References 46 publications
(57 reference statements)
74
461
1
Order By: Relevance
“…We also assume a dipole field configuration and constant plasma density n = 0.5 cm −3 for all runs. We find that, in order to cause precipitation loss of 5 keV CPS electrons in a strong diffusion limit, a chorus intensity of ∼30 pT (L = 8) to 10 pT (L = 10) is required; such amplitudes are rarely detected by THEMIS at these distances in postmidnight sectors [Li et al, 2009;W. Li, private communication, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also assume a dipole field configuration and constant plasma density n = 0.5 cm −3 for all runs. We find that, in order to cause precipitation loss of 5 keV CPS electrons in a strong diffusion limit, a chorus intensity of ∼30 pT (L = 8) to 10 pT (L = 10) is required; such amplitudes are rarely detected by THEMIS at these distances in postmidnight sectors [Li et al, 2009;W. Li, private communication, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Nemzek et al [1995] noted that the minimum plasma density (n > 5 cm −3 ) and the density gradient required by the FCM model were unreachable from geosynchronous data; they are more unlikely to satisfy in the outer magnetosphere; e.g., n was observed as ∼0.3 cm −3 in our event (see Figure 2). Li et al [2009Li et al [ , 2010 found that the chorus wave intensity tends to be rather weak and the plasma density is usually below 1 cm −3 at L∼8-10 in postmidnight sectors (0100-0500 MLT). To make a more quantitative evaluation of the diffusion rate led by the chorus and the ECH wave at L = 8-10, we run a few simulations based upon quasi-linear wave-diffusion theories [e.g., Summers and Thorne, 2003;Lyons, 1974] and simplified models of wave spectra: Ni et al [2008] for the chorus and Horne and Thorne [2000] for the ECH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chorus waves are frequently observed from the nightside through dawn to the dayside equatorial magnetosphere [e.g., Meredith et al, 2001;Li et al, 2009]. Therefore, the chorus wave is a primary candidate that interacts with plasma sheet electrons in the morning sector and causes them to precipitate into the atmosphere.…”
Section: Evaluation Of Theoretical Loss Time Scales Based On Pitch Anmentioning
confidence: 99%
“…The spatial distribution of chorus can give clues about what parameters may affect the excitation of chorus, and has been studied extensively in previous work (e.g., Li et al, 2009;Meredith et al, 2014). Using THEMIS data, Li et al (2009) found that chorus waves have a higher occurrence rate at dayside, although no difference between rising tone and falling tone chorus was made.…”
mentioning
confidence: 99%